UJI DAYA TERIMA NUGGET TEMPE DENGAN PENAMBAHAN JAMUR TIRAM (Pleurotus ostreatus) SEBAGAI MAKANAN ALTERNATIF PENGGANTI DAGING - Nurlani Harahap, Siti; Novianty, Lily; Novina Sukapiring, Dewi (Universitas Cokroaminoto Palopo, 2023)
The nuggets sold in the market are usually made from chicken or beef. However, processed nugget products made from animal protein, namely using chicken and beef, have a high fat content and low fiber, therefore it is necessary to innovate by diversifying animal-based foods with plant-based foods in processed nuggets. This study aims to determine the acceptability of tempe nuggets with the addition of oyster mushrooms as an alternative food to replace meat. The method used in this study was a randomized block design (RBD) which consisted of three treatment levels: P0 = 100% tempeh; P1 = 75% tempe : 25% oyster mushrooms; P2 = 50% tempe : 50% oyster mushrooms; P3 = 25% tempe : 75% oyster mushrooms. Tempe nuggets power test with the addition of oyster mushrooms was carried out using an organoleptic test consisting of 20 panelists with a numerical scale of 5 = very like; 4 = likes; 3 = somewhat like (ordinary); 2=dislike and 1=dislike very much. The P2 treatment, namely 50% tempeh and 50% oyster mushrooms, had the panelist's average preference for taste, aroma, texture and friability of tempeh nuget with the highest value. This could be because the composition might be very good when compared to other compositions.